If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 20y = 0 Solving 16x + 20y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20y' to each side of the equation. 16x + 20y + -20y = 0 + -20y Combine like terms: 20y + -20y = 0 16x + 0 = 0 + -20y 16x = 0 + -20y Remove the zero: 16x = -20y Divide each side by '16'. x = -1.25y Simplifying x = -1.25y
| (x-y)(3x+y)= | | 7/2y-13=-6 | | 4xc-2=c+4 | | x/6-5=x/3-7 | | 5/9x-1/3=1/4 | | 3m -3n/m | | 3(-20)=-60 | | 30(-20)=-60 | | -1/4-(-3/5) | | 3(20)=21 | | 10=4x-7 | | 0.7x+6.52=0.9x+2.12 | | (x-3)(x-4)=34/(33*33) | | 0.7x+6.52=-0.9x+2.12 | | 32x^2-5x-7=0 | | 170=(3x+5)(3x-2) | | 12(3x-3)=3(12x+4) | | 16+2=4+12 | | 9p+11=5p-5 | | 7f-6(f-3)=17 | | 1xy=-12 | | 7(k+4)-6k=28 | | 14=22-0.66x | | 4.4k=29.48 | | (-8y+1)-(-7y-6)=4 | | 7d*3e= | | -20x+20y=100 | | 8e-13=13 | | 8e-13=2 | | 5/x-1+4x/x+1=4 | | 12(3x+3)-5(2x-5)=6x-59 | | 7/5-9/2b= |